Breaking up the Collective Farm : Welfare Outcomes of Vietnam's Massive Land Privatization - Ravallion, Martin (World Bank, Washington, DC, 2014)
The decollectivization of agriculture in Vietnam was a crucial step in the country's transition to a market economy. But the assignment of land use rights had to be decentralized, and local cadres ostensibly had the power to corrupt this process. The authors assess the realized land allocation against explicit counterfactuals, including the simulated allocation implied by a competitive market-based privatization. The authors find that 95-99 percent of maximum aggregate consumption (depending on the region) was realized by a land allocation that reduced overall inequality, with the poorest absolutely better off. They attribute this outcome to initial conditions at the time of reform and actions by the center to curtail the power of local elites.